A Review of Urea Pyrolysis to Produce NH3 Used for NOx Removal. (9th December 2019) - Wang, Denghui; Dong, Ning; Niu, Yanqing; Hui, Shien
Abstract : Urea pyrolysis, from which the denitration reactant ammonia is produced, plays an important role in the urea-based NO x removal process. Research into urea pyrolysis is mostly focused on three parts: urea pyrolysis pathway, catalytic hydrolysis of HNCO, and catalytic pyrolysis of aqueous urea solution. In this paper, detailed overview on research progress of urea pyrolysis was conducted. From the review, it could be concluded that although much research has been carried out, concentration was mainly in analysis of urea pyrolysis products and exploration of catalysts used to improve ammonia yields. Little work has been done on mechanism study and development of a kinetic model with high accuracy, which are still in great need nowadays.